The protective effect and mechanism of (-)-(S)-B-973B on SH-SY5Y cell injury induced by 1-me-thyl-4-phenyl pyridine - LI Huanhuan, QIAO Zhen, WANG Ji, CAO Xiu, DU Xixun (精准医学杂志)
Objective To investigate the protective effect and mechanism of (-)-(S)-B-973B, an allosteric modulator of α7 nicotinic acetylcholine receptor, on SH-SY5Y cell injury induced by 1-methyl-4-phenyl pyridine (MPP+). Methods CCK-8 assay was used to investigate the effect of 0, 100, 200, 300, 500, 1 000, 2 000 μmol/L MPP+ on the viability of SH-SY5Y cells (groups A1-G1, respectively), the effect of 0, 0.1, 1, 3, 10, 30 and 100 μmol/L (-)-(S)-B-973B on the viability of SH-SY5Y cells (groups A2-G2, respectively), and the effect of 0, 0.1, 1, and 3 μmol/L (-)-(S)-B-973B on the viability of SH-SY5Y cells induced by MPP+ (groups B3-E3, respectively). SH-SY5Y cells were divided into control group (group A), MPP+ group (group B), (-)-(S)-B-973B group (group C), (-)-(S)-B-973B+MPP+ group (group D). Flow cytometry was used to observe the effect of on mitochondrial transmembrane potential in groups A-D cells. Western blotting was used to measure the expression le-vel of the superoxide dismutase 1 (SOD1) and Bcl-2/Bax ratio in groups A-D cells. Results CCK-8 assay showed that compared with group A1, groups C1-G1 had a significant reduction in cell viability (F=11.11,t=3.60-6.91,P<0.05); compared with group A2, the groups E2-G2 had a significant reduction in cell viability (F=131.90,t=3.26-20.35,P<0.05), suggesting that (-)-(S)-B-973B with a concentration of above 10 μmol/L had significant toxicity to SH-SY5Y cells; compared with group B3, group D3 had a significant increase in cell viability (F=20.49,t=2.41,P<0.05). Flow cytometry showed that compared with group A, group B had a significant reduction in mitochondrial transmembrane potential (F=4.51,t=2.98,P<0.05), and compared with group B, group D had a significant increase in mitochondrial transmembrane potential (t=3.36,P<0.05). Western blotting showed that compared with group A, group B had a significant reduction in the protein expression level of SOD1 (F=4.61,t=4.19,P<0.05), and compared with group B, group D had a significant increase in the protein expression level of SOD1 (t=2.89,P<0.05); there was no significant difference in Bcl-2/Bax ratio between groups B-D (P>0.05). Conclusion This study shows that (-)-(S)-B-973B exerts a protective effect against SH-SY5Y cell injury induced by MPP+, possibly by enhancing mitochondrial function and exerting an anti-oxidative stress effect.